Intergenerational Learning and the Role of Elders in Integrated Education Systems: Constraints and opportunities for Elder support within the integrated education system and community of the Tr'ondëk Hwëch'in, Dawson City, Yukon - Dempster, Krista (2018)
Education is a tool used to infuse knowledge into the fresh impressionable minds of our present and future citizens. The western imperial approach that has dominated academia is being critically examined for improvement in the face of increasing environmental crisis (Beckford et al., 2010) and decolonization efforts. To continue to adopt the dominant western standards will continue to reproduce the failures of hegemonic colonial ideologies (Aikenhead, 1997; Reid, Teamey, Dillon, 2002:7; Berkes, 1993; Berkes, 2012). Education in the past has been produced, presented and practiced from a euro-centric perspective, and the perspectives of our Indigenous peoples have been perceived as inferior and illegitimate knowledge (Beckford et al, 2010; Barnhardt & Kawagley, 2005). Indigenous knowledge research is recognized nationally and internationally as being an important part of preserving cultural diversity as well as providing important insight into relations such as biology, ecology, resource management, conservation education, development planning, environmental assessment, environmental stewardship, and educational innovation (Berkes, 1993; Berkes, 2012; Battiste, 2002). Knowledge accumulated through long-term inhabitation of a place, such as the knowledge held by Indigenous elders, provides a body of knowledge that can be useful in enriching the education of all children (Barnhardt, 2005). This paper is concerned with intergenerational learning and the role of Elders in integrated education systems. Elder incorporation in school contributes to the maintenance and continuation of intergenerational learning and the resurgence and revitalization of Yukon First Nation culture. Community Elders are what bring Indigenous Knowledge into formal education alongside Euro western theories and practice. This research paper examines what constraints and opportunities are present among First Nations and the school system in this specific community, Tr'ondëk Hwëch'in of Dawson City.